2023
DOI: 10.1101/2023.04.20.537692
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unsaturated fatty acid synthesis is associated with poor prognosis and differentially regulated byMYCNand tumor suppressor microRNAs in neuroblastoma

Abstract: Genetic amplification ofMYCNand disruption of tumor suppressor (TS) microRNA (miRNA) function are central indicators of poor outcome in neuroblastoma (NB). While both MYC family activity and TS miRNAs (TSmiRs) have been broadly implicated in glucose metabolism, their role in unsaturated fatty acid synthesis (UFAS) is poorly understood. We show here that UFAS pathway genesFASN, ELOVL6, SCD, FADS2, andFADS1are overexpressed in human NB cell lines. Based on these data, we show that UFAS are associated with poor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…Our study raises several intriguing questions for future exploration: (1) Is the identified axis of p53 inactivation -astrocyte infiltration -FA metabolism relevant also to primary brain tumors? Glioblastomas commonly inactivate p53 (86), and have been recently shown to depend on FAS (49,(87)(88)(89)(90), suggesting that our findings may be relevant to primary brain tumors as well. ( 2) What is the exact molecular mechanism by which p53 regulates FA metabolism in the context of BCBM?…”
Section: Discussionmentioning
confidence: 76%
“…Our study raises several intriguing questions for future exploration: (1) Is the identified axis of p53 inactivation -astrocyte infiltration -FA metabolism relevant also to primary brain tumors? Glioblastomas commonly inactivate p53 (86), and have been recently shown to depend on FAS (49,(87)(88)(89)(90), suggesting that our findings may be relevant to primary brain tumors as well. ( 2) What is the exact molecular mechanism by which p53 regulates FA metabolism in the context of BCBM?…”
Section: Discussionmentioning
confidence: 76%